2011
DOI: 10.1002/dmrr.1276
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D supplementation on peripheral regulatory T cells and β cell function in healthy humans: a randomized controlled trial

Abstract: A short time high dose vitD3 supplementation significantly increased the frequency of Tregs, but did not further improve β-cell function in apparently healthy subjects. The immunomodulatory potential of vitD might be an important mechanistic link for the association of vitD and T1D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 47 publications
4
68
0
2
Order By: Relevance
“…The vast majority of research in this area, however, has been in animal models or in vitro , and may or may not be reflective of the effects of vitamin D in vivo in humans. There have been a few randomized clinical trials where individuals were supplemented with vitamin D (in cholecalciferol form) and immunological changes studied; only one of these was in healthy individuals 103 , the remaining being in people with MS, 104106 obesity, 107 or congestive heart failure. 108 These studies varied with respect to the dose and duration of vitamin D given and average levels of 25(OH)D achieved (Figure 4).…”
Section: Specific Risk Factorsmentioning
confidence: 99%
“…The vast majority of research in this area, however, has been in animal models or in vitro , and may or may not be reflective of the effects of vitamin D in vivo in humans. There have been a few randomized clinical trials where individuals were supplemented with vitamin D (in cholecalciferol form) and immunological changes studied; only one of these was in healthy individuals 103 , the remaining being in people with MS, 104106 obesity, 107 or congestive heart failure. 108 These studies varied with respect to the dose and duration of vitamin D given and average levels of 25(OH)D achieved (Figure 4).…”
Section: Specific Risk Factorsmentioning
confidence: 99%
“…Following a period of 6-8 month of breast-feeding, infants were randomized into either receiving hydrolyzed casein-based or conventional cow's milk formula 12 . The randomization code will be opened when the last recruited child turns 10 years of age, which is not until 2017 (ref 13) It has been speculated that vitamin D protects against islet autoimmunity, T1D, or both 15 possibly through effects on T lymphocytes 16 . Lower concentrations of vitamin D have been reported in T1D children and lower vitamin D levels during pregnancy were suggested to increase the risk for T1D 17 .…”
Section: Primary Prevention -Treating Subjects At Genetic Risk For Ismentioning
confidence: 99%
“…Alum-formulated recombinant human GAD65 tested in Phase II and III clinical trials were found to be safe [38][39][40] . The immunomodulating effect seemed to include the induction of Treg cells 16,38 and the residual beta-cell function in newly diagnosed T1D patients. We have randomized a total of 50 children in the trial Diabetes Prevention -Immune Tolerance (DIAPREV-IT) to either placebo or alum-formulated GAD65 in a prime and boost design (NCT01122446).…”
Section: Glutamic Acid Decarboxylase (Gad65)mentioning
confidence: 99%
“…Here an improvement in β-cell function could not be confirmed but subjects featured an increase in Treg frequency in the peripheral blood. 15 In view of the clinical application of vitamin D, a balance between an optimal dose and calcaemic side effects needs to be investigated. Current research is focusing on vitamin D analogs that dissociate between an optimal immunomodulatory dose range and toxic calcaemic effects.…”
Section: Ctla4-immunoglobulin Fusion Protein (Abatacept)mentioning
confidence: 99%